Cellular Tower Transporter’ Sustainable Service Level: How to Handle Complaints and Earns Loyalty - Annas, Mohammad; Humairoh (Dinasti Publisher, 2023)
The study aims to uncover the service level of major cellular providers in Indonesia. The stages of the research included the determination of point where cellular towers are built as well as the density of the telecommunication traffic in particular regions in Indonesia. The users of the cellular towers are representatives of the companies from certain logistics establishment that utilizing the existence of the towers. Twelve spots of cellular towers were taken as research objects with 155 users representing their companies who uses and utilizing the cellular towers for various of businesses dominantly in logistics businesses. Structural equation model analysis were implemented to seek the affects of each variables. The result showed that all the data collected were supporting the hypotheses and this result were also showed that loyalty towards service delivered and complaints might occur parallelly.